Reclaiming Thecla an introduction to the Acts of Thecla - Skemp, Vincent T. M. 1967-; Christ, Gina (Claremont, CA Claremont Press, 2022)
Reclaiming Thecla is an introduction to the second-century Christian work the Acts of Thecla, which is embedded in the apocryphal Acts of Paul. This short book guides readers through the cultural and theological settings out of which the text arose. The authors explain debates about the text, provide their own views, and argue that this story can still teach us today by helping us engage in conversations about Christian identity, love, gender constructions, and female discipleship
Homer's Odyssey and Euripides's Hippolytus.
Includes bibliographical references (pages 159-175) and indexes (pages 177-190)
Keywords: Thecla -- Saint -- Legends -- History and criticism; Paul -- the Apostle, Saint -- Legends -- History and criticism; Paul - the Apostle, Saint; Thecla - Saint; Acts of Paul and Thecla -- Commentaries; Acts of Paul and Thecla -- Criticism and interpretation; Acts of Paul and Thecla; Greek literature -- Relation to the New Testament; Christian literature, Early -- Greek authors; Littérature grecque - Relation avec le Nouveau Testament; Littérature chrétienne primitive - Auteurs grecs; RELIGION - Biblical Studies - Bible Study Guides; RELIGION - Theology; Christian literature, Early - Greek authors; Greek literature - Relation to the New Testament; Legends; Commentaries; Criticism, interpretation, etc; Einführung